Macroeconomic variables on non-performing loans bank in Malaysia / Norhazrina Ibrahim - Ibrahim, Norhazrina (Faculty of Business and Management, 2019)
The fluctuation of non-performing loans in Malaysia has gains the interest to this research to find out the causes of unstable trend. This paper is to investigate the relationship between the microeconomic variables on non-performing loans bank in Malaysia with lending rate, inflation rate, exchange rate, unemployment rate and gross domestic product. Secondary data was collected from World Bank Indicator and Index Mundi Malaysia from year 2010 to 2017 which is total 8 years. As the type of data gathered is on monthly basis, there are 96 observations to be tested in this research. Plus, Ordinary Least Square (OLS) method was employed to run the model and estimate the regression. Evidently, results reveal that there is statistically significant relationship impact of non-performing loans towards lending rate, inflation rate, exchange rate and gross domestic product. Besides that, the results also reveal that there is insignificant relationship impact of non-perfoming loans towards unemployment. These empirical results help investors to determine the factors that could affect the non-performing loans and to make a decision making.